2019
DOI: 10.1136/bjophthalmol-2018-313493
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biomechanics and biomechanically corrected intraocular pressure in primary open-angle glaucoma, ocular hypertension and controls

Abstract: AimsTo compare the biomechanically corrected intraocular pressure (IOP) estimate (bIOP) provided by the Corvis-ST with Goldmann applanation tonometry (GAT-IOP) in patients with high-tension and normal-tension primary open-angle glaucoma (POAG; HTG and NTG), ocular hypertension (OHT) and controls. Moreover, we compared dynamic corneal response parameters (DCRs) of the Corvis-ST in POAG, OHT and controls, evaluated the correlation between global visual field parameters mean deviation and pattern SD (MD and PSD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 33 publications
(35 reference statements)
4
59
2
2
Order By: Relevance
“…16 Several previous studies showed differences in the dynamic Scheimpflug biomechanical parameters between healthy and glaucoma eyes. [17][18][19][20][21] However, these results are conflicting with respect to the biomechanical changes associated with glaucoma. [17][18][19][20][21] Part of the discrepancy may be explained by the confounding effects of baseline factors such as age, IOP, type of disease, and axial length.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Several previous studies showed differences in the dynamic Scheimpflug biomechanical parameters between healthy and glaucoma eyes. [17][18][19][20][21] However, these results are conflicting with respect to the biomechanical changes associated with glaucoma. [17][18][19][20][21] Part of the discrepancy may be explained by the confounding effects of baseline factors such as age, IOP, type of disease, and axial length.…”
mentioning
confidence: 99%
“…[17][18][19][20][21] However, these results are conflicting with respect to the biomechanical changes associated with glaucoma. [17][18][19][20][21] Part of the discrepancy may be explained by the confounding effects of baseline factors such as age, IOP, type of disease, and axial length. 16,22 For example, most prior studies included glaucoma patients with high baseline 18,19 or relatively high treated IOP.…”
mentioning
confidence: 99%
“…Bereits seit Längerem ist bekannt, dass die Biomechanik der Augenhülle bei Offenwinkelglaukomen verändert ist [18]. Auch mit dem Corvis ST konnten in verschiedenen Arbeiten signifikante Unterschiede von Biomechanikparametern zwischen gesunden und pathologischen Patientenkollektiven festgestellt werden [19]. Wieder stellte sich die Frage, inwiefern Machine-Learning-Algorithmen bei der Entwicklung eines Gesamtparameters behilflich sein könnten.…”
Section: Glaukom-screening Anhand Der Kornealen Biomechanikunclassified
“…And the biomechanical corrected IOP (bIOP) [31] is purported to be less dependent on biomechanical properties. At present, there are some researches to further explore and verify the IOP measurement of bIOP in healthy people [32] , glaucoma [33] and even keratoconus patients [32] . In addition, it has been proposed [34] that bIOP is able to reduce the known correlation between CCT and IOP readings before and after refractive surgery, such as LASIK and small-incision lenticule extraction (SMILE) [34] .…”
Section: Comparison Of Iop Pre-and Post-operative Surgerymentioning
confidence: 99%